2015
DOI: 10.1051/fruits/2015026
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of generative development in early maturing litchi ‘Early Big’, a novel cultivar in Taiwan

Abstract: -Introduction.A short harvest window is common in litchi production worldwide, leading to imbalance between supply and demand for fresh fruit. This problem can be mitigated with early-maturing cultivars, such as 'Early Big', released in 2010 in Taiwan. Our goal was to characterize the generative development in this novel litchi cultivar. Materials and methods. The patterns of female flowering and fruit development, and fruit abscission were investigated in 'Early Big' litchi in 2013 and 2014. The relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The prevailing temperature as well as phenol content and age of plants significantly affect flowering. The success of fruit set depends on male parents (Lal et al, 2019a,b), time of pollination (Lal et al, 2021a) and poor fruit retention is due to fruit drop (Chang et al, 2015). Litchi is a good source of vitamin C (Marboh et al, 2019).…”
mentioning
confidence: 99%
“…The prevailing temperature as well as phenol content and age of plants significantly affect flowering. The success of fruit set depends on male parents (Lal et al, 2019a,b), time of pollination (Lal et al, 2021a) and poor fruit retention is due to fruit drop (Chang et al, 2015). Litchi is a good source of vitamin C (Marboh et al, 2019).…”
mentioning
confidence: 99%
“…The initial drop comprised mostly of un-pollinated flowers as the lifespan of individual litchi flowers were very short and many flowers were apparently not pollinated during their receptive period. Chang et al (2015) also reported massive fruit drop in litchi. Mehdi et al (2007) also found that improper pollination and fertilization caused heavy fruit drop, small proportion (0.1-0.25%) set fruit and reached maturity.…”
Section: Resultsmentioning
confidence: 92%
“…Litchi starts flowering during February-March in Bihar conditions, and the intensity of flowering depends on temperature during floral bud differentiation, previous years fruiting and phenol content and age of plants (Lal et al, 2019a;. A single panicle can produce hundreds of flowers (M1 flowers, Female flowers and M2 flowers) and the success of fruit set depends on the pollen grain received from male parents (Lal et al, 2019b) and poor fruit retention due to fruit drop (Chang et al, 2015). The litchi fruit consists of about 55-85% pulp, 6-27% seed and 10-28% peel which varies depending upon cultivar and climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…What remains to be seen is how much this interferes with the physiological quality of the seeds. Chang et al (2015) report late ripening fruits may have smaller seeds and a higher proportion of wrinkled seeds. Other reports highlight wrinkling caused by embryo abortion resulting from stenospermocarpy (Huang and Qiu, 1987) and in addition to liquid endosperm collapse and competition for nutrients between the pulp and embryo (Lee and Chang, 2014).…”
Section: Parametersmentioning
confidence: 99%